Is Antibody-Dependent Enhancement of Trypanosoma cruzi Infection Contributing to Congenital/Neonatal Chagas Disease? - Carlier, Yves; Truyens, Carine; Muraille, Eric (Frontiers in Immunology, 2021)
The newborns of women infected with the parasite Trypanosoma cruzi (the agent of Chagas disease) can be infected either before birth (congenitally), or after birth (as e.g., by vector route). Congenital Chagas disease can induce high levels of neonatal morbidity and mortality. Parasite-infected pregnant women transmit antibodies to their fetus. Antibodies, by opsonizing parasites, can promote phagocytosis and killing of T. cruzi by cells expressing FcγR, on the mandatory condition that such cells are sufficiently activated in an inflammatory context. Antibody-dependent enhancement (ADE) is a mechanism by which antibodies enhance entry of infectious agents into host cells by exploiting the phagocytic FcγR pathway. Previously reported Chagas disease studies highlighted a severe reduction of the maternal-fetal/neonatal inflammatory context in parasite-transmitting pregnant women and their congenitally infected newborns. Otherwise, experimental observations brought to light ADE of T. cruzi infection (involving FcγR) in mouse pups displaying maternally transferred antibodies, out of an inflammatory context. Herein, based on such data, we discuss the previously unconsidered possibility of a role of ADE in the trans-placental parasite transmission, and/or the development of severe and mortal clinical forms of congenital/neonatal Chagas disease in newborns of T. cruzi-infected mothers.